Business analysis for practitioners : a practice guide (Project Management Institute, 2015)
Recent research has shown that organizations continue to experience project issues associated with the poor performance of requirements-related activities-a core task for the practice of business analysis. In fact, poor requirements practices are often cited as a leading cause of project failure in PMI's Pulse of the Profession™ surveys. Business Analysis for Practitioners: A Practice Guide provides practical resources to tackle the project-related issues associated with requirements and business analysis-and addresses a critical need in the industry for more guidance in this area. The practice guide begins by describing the work of business analysis. It identifies the tasks that are performed, in addition to the essential knowledge and skills needed to effectively perform business analysis on programs and projects.